Effects of Ward Noise Reduction Administration on Mental Health and Lung Function of Patients with Lung Cancer - Lina Liu; Shuo Cai; Xiaoyu Wu; Huixin Zhu; Yu Wang (Noise and Health)
Objective: This study aimed to analyze the effects of ward noise reduction administration on the lung function and mental health of patients with lung cancer. Methods: A total of 195 patients who underwent lung cancer surgery in PLA Northern Theater Command Air Force Hospital from November 2020 to November 2022 were selected to be divided into a control group (routine nursing) and an observation group (routine nursing and ward noise reduction administration) in accordance with the medical record system. The general demographic data, noise level, lung function (forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC) and FEV1/FVC)), and complications of patients in the two groups were collected. Propensity score matching (PSM) was used to balance the baseline data of the two groups, and t-test and chi-square test were used to analyze the data. Results: After PSM was conducted, 50 patients were enrolled in each group. No statistical difference was found in the baseline data, preadministration noise levels, and FEV1, FVC, FEV1/FVC, state-anxiety inventory (S-AI), and trait anxiety inventory scale (T-AI) scores between the two groups (P > 0.05). After ward noise reduction was administered, the noise level in the observation group was lower than that in the control group (P < 0.05). The FEV1, FVC, and FEV1/FVC scores of the observation group were higher than those of the control group but were not statistically significant (P > 0.05). The S-AI and T-AI scores of the observation group were lower than those of the control group (P < 0.05). No differences were found in the complications between the two groups (P > 0.05). Conclusion: Administering ward noise reduction in patients with lung cancer can alleviate their negative emotions, thus worthy of clinical adoption.